Biossorção de corante vermelho 40 por leveduras magnetizadas com nanopartículas de óxido de ferro - Pereira, Tamara de Freitas (2019)
Azo dyes are a class of organic dyes most commonly used industrially. Because of this, they represent a large group of water-polluting agents that appear in effluents from the coloring of fabrics, leather, paper, paints, food, cosmetics, among other. Removal of these waste water dyes has been a major environmental challenge due to its toxic potential and aesthetic impact. Considering the above, the objective of this study was to evaluate the adsorptive capacity of the yeast (Saccharomyces cerevisiae) magnetized with nanoparticles of iron, azo dye 40, in aqueous solution. Morphological, chemical and structural characterizations of the biosorbent were carried out. The biosorption process was carried out in a batch at room temperature (25 ° C) where the concentrations of 25, 50, 100, 150 and 200 mg L-1 of dye were tested for 0,05 g of magnetized yeast. The conditions of the tests were varied in relation to pH (2,0-5,0) and contact time (480 minutes), to obtain the optimum pH and equilibrium time of the biosorption process. The models of pseudo-first order, pseudo-second order and Elovich were used to evaluate the data obtained in the kinetic study. The isotherms models of Langmuir, Freundlich, Temkin and Dubinin-Radushkevich were used to better understand the mechanism of biosorption. Desorption/readsorption analyzes of this biosorbent were also carried out. Among the structural and morphological analyzes, the point of zero charge obtained by the magnetized yeast was 5.5, which indicated a positively charged surface when it was found in the dye solution at pH 2.0. It was observed in electron microscopy, a smooth and rounded surface yeast; and when it was magnetized, it was possible to perceive this whole surface covered by the nanoparticles of iron oxide, giving it the magnetic property. In the analysis of chemical composition, significant differences were observed in the region between 1600-800 cm-1, indicating that the functional groups of this region worked more actively during the biosorption process, being they responsible for the binding of the magnetized yeast with the red dye 40 (C=C, S=O e C–H). The optimum pH was 2,0 and the equilibrium time was reached in 240 min with 89% dye removal. Through the determination of the point of zero charge it was suggested that when the magnetized yeast came into contact with the dye solution at pH 2,0, the surface of the same was positively charged, attracting molecules of anionic dyes. The best data adjustment was given by the kinetic model of pseudo-second order (R2= 0,999), being able to predict the kinetic behavior during the entire adsorption time; and the Freundlich isotherm (R2= 0,97). Regarding the desorption/readsorption analyzes, the magnetized yeast was not considered efficient for reuse.